Expression of SRC-1, AIB1, and PEA3 in HER2 mediated endocrine resistant breast cancer; a predictive role for SRC-1. Issue 10 (27th September 2004) - Fleming, F J; Myers, E; Kelly, G; Crotty, T B; McDermott, E W; O'Higgins, N J; Hill, A D K; Young, L S
Abstract : Background: In human breast cancer, the growth factor receptor HER2 is associated with disease progression and resistance to endocrine treatment. Growth factor induced mitogen activated protein kinase activity can phosphorylate not only the oestrogen receptor, but also its coactivator proteins AIB1 and SRC-1. Aim: To determine whether insensitivity to endocrine treatment in HER2 positive patients is associated with enhanced expression of coactivator proteins, expression of the HER2 transcriptional regulator, PEA3, and coregulatory proteins, AIB1 and SRC-1, was assessed in a cohort of patients with breast cancer of known HER2 status. Methods: PEA3, AIB1, and SRC-1 protein expression in 70 primary breast tumours of known HER2 status (HER2 positive, n = 35) and six reduction mammoplasties was assessed using immunohistochemistry. Colocalisation of PEA3 with AIB1 and SRC-1 was determined using immunofluorescence. Expression of PEA3, AIB1, and SRC-1 was correlated with clinicopathological parameters. Results: In primary breast tumours expression of PEA3, AIB1, and SRC-1 was associated with HER2 status (p = 0.0486, p = 0.0444, and p = 0.0012, respectively). In the HER2 positive population, PEA3 expression was associated with SRC-1 (p = 0.0354), and both PEA3 and SRC-1 were significantly associated with recurrence on univariate analysis (p = 0.0345; p<0.0001). On multivariate analysis, SRC-1 was significantly associated with disease recurrence in HER2 positive patients (p = 0.0066). Conclusion: Patients with high expression of HER2 in combination with SRC-1 have a greater probability of recurrence on endocrine treatment compared with those who are HER2 positive but SRC-1 negative. SRC-1 may be an important predictive indicator and therapeutic target in breast cancer.